2018
DOI: 10.1103/physrevlett.121.138001
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Geometrical and Kinematic Contributions to the Silo Clogging Process

Abstract: Based on the implementation of a novel silo discharge procedure, we are able to control the grains velocities regardless of the outlet size. This allows isolating the geometrical and kinematic contributions to the clogging process. We find that, for a given outlet size, reducing the grains velocities to extremely low values leads to a clogging probability increment of almost two orders of magnitude, hence revealing the importance of particle kinematics in the silo clogging process. Then, we explore the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Nevertheless, we still expect that hopper geometries lead to clogging reduction for a polydisperse sample as the restriction imposed by the hopper in the angles between particles holds in this case. Also, other features such as the extrapolation to a three-dimensional case, or the effect of the particles' dynamics [33] (which could slightly vary in the range of 3 < D/d 4 leading to changes in the mean avalanche size) should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we still expect that hopper geometries lead to clogging reduction for a polydisperse sample as the restriction imposed by the hopper in the angles between particles holds in this case. Also, other features such as the extrapolation to a three-dimensional case, or the effect of the particles' dynamics [33] (which could slightly vary in the range of 3 < D/d 4 leading to changes in the mean avalanche size) should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The fitting results ( H / d p , α ( H / d p )) are plotted in Figure 7(d) as red scatters. Since exponential relationships are broadly used to analyze clogging or jamming problems, 63,64,65 we adopt the exponential function to quantify the dependence of α on H / d p , α=ea+b()normalH/dp, where a = − 4.19 ± 0.22, b = 0.41 ± 0.042 are fitting parameters. Equation () is displayed as the black line in Figure 7(d) and shows high fitting accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…J inf represents the clogging probability when h tends towards infinity. is value depends on other parameters (like orifice size) of the system, and there exist some empirical models of this value [11]. C 1 and C 2 are the fitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…From the pioneering work of To et al in 2001 [6], we know that magnitude of clogging probability J changes greatly with the outlet size. Furthermore, the existence of a critical outlet size above which the flow may never get jammed remains debatable [11]. Subsequently, it has been experimentally and numerically shown that some methods can reduce the probability of clogging by, for example, putting an obstacle above the exit [12,13] and applying a helical texture to the pipes' inner wall [14].…”
Section: Introductionmentioning
confidence: 99%